Clinical features of dystonia in atypical parkinsonism - Godeiro-Junior, Clecio [UNIFESP] (2008)
BACKGROUND: The association between Dystonia and Parkinson's disease (PD) has been well described especially for foot and hand dystonia. There is however few data on dystonic postures in patients with atypical parkinsonism. OBJECTIVE: To evaluate the frequency and pattern of dystonia in a group of patients with atypical parkinsonism (multiple system atrophy - MSA, progressive supranuclear palsy - PSP, and corticobasal degeneration - CBD) and to investigate whether dystonia could be the first presenting symptom at disease onset in those patients. METHOD: A total of 38 medical charts were reviewed (n=23/MSA group; n=7/CBD group; n=8/PSP group) and data values were described as means/standard deviations. The variables evaluated were sex, age at onset, disease duration, first symptom, clinical features of dystonia and other neurological signs, response to levodopatherapy, Hoehn&Yahr scale >3 after three years of disease, and magnetic resonance imaging findings. RESULTS: The overall frequency of dystonia in our sample was 50% with 30.4% (n=7) in the MSA group, 62.5% (n=5) in the PSP group, and 100% (n=8) in the CBD group. In none of these patients, dystonia was the first complaint. Several types of dystonia were found: camptocormia, retrocollis, anterocollis, blepharoespasm, oromandibular, and foot/hand dystonia. CONCLUSION: In our series, dystonia was a common feature in atypical parkinsonism (overall frequency of 50%) and it was part of the natural history although not the first symptom at disease onset. Neuroimaging abnormalities are not necessarily related to focal dystonia, and levodopa therapy did not influence the pattern of dystonia in our group of patients.